Molecular Characterization of MyD88 in Anodonta woodiana and Its Involvement in the Innate Immune Response to Bacterial Infection - Qu, Fufa; She, Qing; Li, Jialing; Zeng, Xuan; Li, Yumiao; Liu, Xinyu; Ren, Lingxin; Liu, Zhenzhen; Gao, Chaoran; Lu, Xinyu; Long, Mengyao; Li, Xinya (Frontiers in Immunology, 2022)
Myeloid differentiation factor 88 (MyD88) is a key adapter molecule in Toll-like receptor signal transduction that triggers downstream immune cascades involved in the host defense response to exogenous pathogens. However, the function of MyD88s in mollusks, especially in freshwater shellfish, remains poorly understood. In this study, a novel freshwater shellfish MyD88 (denoted AwMyD88) was characterized from Anodonta woodiana. The present AwMyD88 protein consists of 474 amino acids and contains a conserved a typical death domain (DD) and a conservative Toll/IL-1R (TIR) domain with three typical boxes. Quantitative real-time PCR (qRT-PCR) analysis showed that AwMyD88 was broadly expressed in all the examined tissues, and the highest expression level was observed in hemocytes of A. woodiana. When challenged with Aeromonas hydrophila and lipopolysaccharide (LPS), the mRNA expression levels of AwMyD88 were significantly induced in hemocytes of A. woodiana in vivo and in vitro. In addition, in vivo injection experiments revealed that MyD88 signaling pathway genes showed strong responsiveness to A. hydrophila challenge, and their expression levels were significantly upregulated in hemocytes. Knockdown of AwMyD88 reduced the transcript levels of immune related transcription factors (AwNF-κB and AwAP-1) and effectors (AwTNF, AwLYZ, AwDefense and AwAIF) during A. hydrophila infection. Moreover, subcellular localization analysis indicated that AwMyD88 was mainly localized to the cytoplasm in HEK293T cells. Finally, luciferase reporter assays revealed that AwMyD88 associates with AwTLR to activate the NF-κB and AP-1 signaling pathways in HEK293T cells. These results suggested that AwMyD88 might be involved in the host defense response to bacterial challenge, providing new insight into the immune function of the MyD88 signaling pathway in freshwater shellfish.